Low Molecular Weight Oligomers of Poly(alkylene succinate) Polyesters as Plasticizers in Poly(vinyl alcohol) Based Pharmaceutical Applications - Palamidi, Artemis (Polymers (Basel), 2021)
The plasticizing effect of three low molecular weight oligomers of aliphatic poly(alkylene succinate) polyesters, namely poly(butylene succinate) (PBSu), poly(ethylene succinate) (PESu), and poly(propylene succinate) (PPSu), on partially hydrolyzed poly(vinyl alcohol) (PVA) used in melt-based pharmaceutical applications, was evaluated for the first time. Initially, the three aliphatic polyesters were prepared by the melt polycondensation process and characterized by differential scanning calorimetry (DSC), (1)H NMR, intrinsic viscosity, and size exclusion chromatography (SEC). Subsequently, their effect on the thermophysical and physicochemical properties of PVA was thoroughly evaluated. According to the obtained results, PVA was completely miscible with all three polyesters, while PESu induced PVA’s thermal degradation, with the phenomenon starting from ~220 °C, in contrast to PBSu and PPSu, where a thermal profile similar to PVA was observed. Furthermore, molecular interactions between PVA and the prepared poly(alkylene succinate) polyesters were revealed by DSC, ATR-FTIR, and molecular dynamics simulations. Finally, melt flow index (MFI) measurements showed that, in contrast to PBSu, the use of PESu or PPSu significantly improved PVA’s melt flow properties. Hence, according to findings of the present work, only the use of low molecular weight PPSu is suitable in order to reduce processing temperature of PVA and improve its melt flow properties (plasticizing ability) without affecting its thermal decomposition.